POLITENESS STRATEGIES IN NBC’S “LITTLE BIG SHOTS” PROGRAM - Majid, Fauzi Bin Abdul; Sunarto, Emanuel (International Journal of Humanity Studies (IJHS), 2025)
This study explores politeness strategies in intergenerational media interactions, a conversational exchange between the host Steve Harvey and three-year-old James, the youngest mayor of Dorset, Minnesota, on NBC’s Little Big Shots TV program.  The study is based on Brown-Levinson’s politeness theory (1987). Using a descriptive qualitative approach, the research examined how politeness strategies are employed in a media environment involving a child participant and shows the delicate balance among entertainment goals, institutional discourse, and face preservation. The results uncover sophisticated applications of the four strategies of politeness, namely bald on record, positive politeness, negative politeness, and off-record strategies that make communication across age differences effective while upholding audience engagement and participant comfort. The findings offer insights into how subtle communicative tactics are used to play social roles, uphold institutional esteem, and foster authentic adult-child interactions in television programming.